Dukungan Organisasi, Budaya Sekolah dan Kompetensi Guru untuk menjamin Kinerja Kepala Sekolah Di Sekolah Dasar Kecamatan Magelang Selatan - Pratiwi Anggraeni; Welius Purbonuswanto; Jumintono (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to determine (1) The influence of organizational support on the performance of the principal; (2) The influence of school culture on the performance of the principal; (3) The influence of teacher competence on the performance of the principal; (4) The influence of organizational support, school culture and teacher competence on the performance of the principal of Elementary Schools in South Magelang District. The approach used in this study is quantitative, with a survey method. The hypothesis was tested using multiple linear regression analysis. The population in this study was 168 elementary school teachers throughout South Magelang District, with sampling using the proportional random sampling technique, a sample of 114 teachers was obtained. The collected data were analyzed using SPSS, which consists of data analysis techniques and prerequisite tests consisting of normality tests, linearity tests, multicollinearity tests. For the hypothesis test using multiple linear regression, R test, t test, and F test. The results show that organizational support, school culture, and teacher competence have a positive and significant effect on the performance of the principal at Elementary Schools in South Magelang District, both partially and simultaneously